The perceived role of coaching in enhancing millennial leaders’ development in South Africa - Malunga, Nobuhle (My University, 2019)
One of the key strategies of maintaining organisational performance is investing in the development of leaders. Coaching is one of the instruments that has been used as a process to positively influence leader development. Coaching has been labelled as a process that assists leaders to modify behaviour and perspectives without sacrificing on competence and self-esteem. This study considered the rise of the millennial generation in the South African workforce, particularly in leadership positions across industries. The primary aim of this study was to investigate and describe the millennial leaders’ perception of executive coaching and its role in effectively advancing their leader journey. Millennials have been described as the latest generation to enter the workforce, which is inclusive of individuals born between 1980 and 2000. In 1990, the South African landscape changed, demanding an inclusive workforce, through ensuring a representation of race, gender and age. It is argued however that business has been slow to realise that the political changes influenced societal and behavioural trends and in turn the diverse make up and management of talent within organisations. This report therefore paid attention to the experiences leaders within South Africa had while being coached. This was done by looking at the challenges before engaging in the coaching process and the perceived value and impact that the leader derived from coaching. The study assumed a qualitative design, using interviews with eight millennials in senior management positions. Interviews were then analysed thematically. The study suggested that the leaders perceived coaching as a process that had a significant impact towards their leader journey - one that has positive psychological effects in their work and home life. Furthermore, the study suggested that coaching millennials is not significantly different to coaching the generations before but that coaches need to be mindful of how the millennials prefer to be engaged. The process of self-reflection was reported by most participants as the phase during the coaching process that allowed them to reach their best self as developed leaders. Therefore, one of the study recommendations is that coaches, regardless of the coaching process used, must ensure that self-reflection is always one of the coaching instruments used during the coaching process - particularly when engaging with millennial coachees.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Business Executive Coaching, Johannesburg 2019
Keywords: Executive coaching; Executives--Training of; Career development